Analysis of lifecycle models and Software Component Retrieval - Monisha Kumari; Dimple Nagpal (Universitas Lampung, 2018)
The development of the software component consists of many stages and the lifecycle models show the flow of the stages that the development of the component follows. The development of the new software from the reusable software component has been challenging as it is always a concern to retrieve the relevant software component from the repository. There are lifecycles for making the design and development of the component more efficient. In this paper, an overview of the software component lifecycle models X-model, Y-model, Z-model, knot model and elite model and phases explanation of the lifecycle has been discussed. The current concept explains the comparison of the three lifecycle models in this paper. The component retrieval algorithms has been compared and discussed for the retrieval of the software component.